Decoding Artificial Intelligence in Neuroscience: Applications Beyond Diagnosis - Salave, Sagar; Rana, Dhwani; Benival, Derajram; Jain, Aakanchha (Current Indian Science, 2023)
Background Artificial Intelligence has witnessed exponential expansion in health care applications. The article pronounces the dynamic excellence AI is achieving in the healthcare discipline of neuroscience. Objective The paper highlights basic concepts of AI and acmes the interdisciplinary collaboration of Computational neuroscience, Cognitive science, and AI. Also, the article draws out important findings related to AI in neuroscience amongst its diverse application in the various disciplines. An ephemeral overview of applications of AI-based constructs in neurological disorders namely Neuroinflammation, Schizophrenia, Parkinson’s disease, Epilepsy, Autism spectrum disorder, Alzheimer’s disease, Brain tumor and Anesthesiology has been demonstrated in the present work. Methods The method includes the collection of data from different search engines like google Scholar, PubMed, ScienceDirect, SciFinder, etc. to get coverage of relevant literature for accumulating appropriate information regarding AI, neuroscience, and their linkages. Results These considerations are made to expand the existing literature on the progressing role of AI in the management of neurological disorders. Conclusion The exponential expansion in the development of AI-based systems might aid in addressing the prevailing limitations in the domain of neurological disorders and neuroscience.
Keywords: Neurology